Diabetes self‐management and its related factors among Chinese young adults with type 2 diabetes mellitus - Qiao He; Yu Liu; Keke Lin; Fang Zhao; Hong Guo; Yina Shen (Wiley, 2023)
Abstract Aim To explore the status quo of self‐management among young adults with type 2 diabetes mellitus (T2DM) and the determinants of self‐management under the guidance of social cognitive theory. Design A cross‐sectional study. Methods In total, 227 young adults (18-44 years old) with T2DM at two hospitals in Beijing completed the questionnaires. The Summary of Diabetes Self‐care Activities (SDSCA) was used, along with additional questionnaires about diabetes self‐efficacy, attitude, diabetes distress, diabetes knowledge, coping styles and social support. Univariate analysis and multiple linear regression were used to explore the related factors of self‐management among the young patients. Results The scores for the SDSCA in diet, exercise, blood‐glucose testing, foot care and medication taking were (4.16 ± 1.51), (3.46 ± 2.50), (2.28 ± 2.24), (1.08 ± 1.84) and (6.09 ± 1.88), respectively. Stepwise multiple linear regression showed that fasting blood‐glucose value was significantly associated with self‐management behaviours of diet, exercise, blood‐glucose testing and medication taking. Self‐efficacy was significantly associated with self‐management behaviours of diet, exercise and foot care. Diabetes distress, diabetes‐related social activity, confrontation, education, duration of T2DM, treatment modalities and diabetes knowledge were associated with the one or two dimensions of SDSCA in the young adults with T2DM.